Skiing - Evans, Jeremy (London : Heinemann, 1992)
Discusses the fundamentals of skiing, what to wear, competitions, and international resorts.
First published by Heinemann Children's Reference, 1991.
Includes index.
Elementary School Library Collection (Bro-Dart).
Horn Book Magazine.
6.7
5-8.
Keywords: Skis and skiing -- Juvenile literature; Skis and skiing; Skis and Skiing